KEBERANJAKAN FATWA DARI LEGAL OPINION MENJADI LEGAL BINDING: (Studi Kasus Fatwa DSN MUI Tentang Perbankan Syariah) - Wildan Imaduddin Muhammad (Jurisprudensi : Jurnal Ilmu Syariah, Perundangan-Undangan dan Ekonomi Islam, 2019)
The basic concept of fatwa in its position of binding law is legal opinion in Indonesia. But in certain cases fatwa has a legal binding which is must be obeyed by people. This article demonstrate how fatwa has a legal binding in the context of Indonesia. The objects of research specifically is banking sharia act in which it is said Islamic economy activities must be appropriate with the fatwa of national sharia council. As concluding remark, this article show the development of fatwa from legal opinion to legal binding through the constitution as represent by sharia banking act.